2016
DOI: 10.1002/eqe.2751
|View full text |Cite
|
Sign up to set email alerts
|

Vertical acceleration demands on column lines of steel moment‐resisting frames

Abstract: Summary In this paper, vertical peak floor acceleration (PFAv) demands on elastic multistory buildings are statistically evaluated using recorded ground motions. These demands are applicable to the assessment of nonstructural components that are rigid in the vertical direction and located at column lines or next to columns. Hence, PFAv demands of the floor system away from column lines and their effects on nonstructural components are not addressed. This study is motivated by the questionable general assumptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Furthermore, it is apparent that the taller frame structures exhibit the largest median PFA v to PGA v ratio with its maximum value of 4.8 at the roof level of the center node of the left bay of the 20-story frame structure. This large amplification is in accordance with results of Moschen et al (2016) and Francis et al (2017). Moschen et al (2016) computed the vertical accelerations of a generic stick model, representing the interior column line of a steel frame, in an effort to assess the vertical accelerations at or very close to column lines.…”
Section: Normalized Peak Floor Acceleration Demand Of the Base Case Frame Modelssupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, it is apparent that the taller frame structures exhibit the largest median PFA v to PGA v ratio with its maximum value of 4.8 at the roof level of the center node of the left bay of the 20-story frame structure. This large amplification is in accordance with results of Moschen et al (2016) and Francis et al (2017). Moschen et al (2016) computed the vertical accelerations of a generic stick model, representing the interior column line of a steel frame, in an effort to assess the vertical accelerations at or very close to column lines.…”
Section: Normalized Peak Floor Acceleration Demand Of the Base Case Frame Modelssupporting
confidence: 93%
“…Hence, neglecting the filtering effect of the building on the vertical base excitation component of ground motion would in some cases underestimate the magnitude of vertical NSC acceleration demands. A recent study by Moschen et al (2016) of the vertical peak floor acceleration (PFA v ) demand of a generic stick model, representing the column line of steel perimeter moment resisting frames, confirmed these considerations. It was found that the median PFA v demand at column lines can be up to four times larger than the vertical peak ground acceleration (PGA v ).…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Bradley, 2013; Lin et al, 2013) are available in the literature, little effort has been devoted to developing methods for the selection of hazard consistent vertical ground motion records. In engineering practice, however, there are many examples where the vertical component of the ground motion, in addition to the horizontal ones, plays a significant role on the structural seismic response: reinforced concrete precast structures (Bovo and Savoia, 2019), dams (Chakrabarti and Chopra, 1972; Chopra, 1966; Christopoulos et al, 2003), components in nuclear power plants (Kitamura et al, 2005), rocking systems (Vrettos, 1999), and non-structural components (Moschen et al, 2016), such as suspended ceilings and other contents sensitive to rocking, sliding, or overturning.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the results of this paper are summarized based on the comparison methodology in references [26,27]. Tables 9 and 10 show that the peak vertical floor acceleration (named as PFAv) may exceed the peak vertical ground acceleration (named as PGAv).…”
Section: Elastic Beam-column Elementmentioning
confidence: 99%